2020
DOI: 10.1101/2020.07.14.203505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversity in rest-activity patterns among Lake Malawi cichlid fishes suggests novel axis of habitat partitioning

Abstract: Animals display remarkable diversity in rest and activity patterns that are regulated by endogenous foraging strategies, social behaviors, and predator avoidance. Alteration in the circadian timing of activity or the duration of rest-wake cycles provide a central mechanism for animals to exploit novel niches. The diversity of the 3000 cichlid species throughout the world provides a unique opportunity to examine variation in locomotor activity and rest. Lake Malawi alone is home to over 500 species of cichlids … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…LF therefore appear to develop a more athletic heart, running counter to our initial expectation that LF is a more efficient forager and should therefore expend less overall energy while feeding, compared to TRC (Conith et al, 2019a). Both species are territorial, with males vigorously defending breeding territories (Ribbink et al, 1983), and a recent study examining activity levels across cichlid species found that LF and TRC exhibit high and indistinguishable levels of activity relative to other species (Lloyd et al, 2020). LF do occupy a greater depth range relative to TRC, foraging up to depths of 18 metres, while TRC often occupy depths up to 6 metres (Ribbink et al, 1983).…”
Section: Morphological Variation Among Hybrids Mimics Variation Obsmentioning
confidence: 57%
“…LF therefore appear to develop a more athletic heart, running counter to our initial expectation that LF is a more efficient forager and should therefore expend less overall energy while feeding, compared to TRC (Conith et al, 2019a). Both species are territorial, with males vigorously defending breeding territories (Ribbink et al, 1983), and a recent study examining activity levels across cichlid species found that LF and TRC exhibit high and indistinguishable levels of activity relative to other species (Lloyd et al, 2020). LF do occupy a greater depth range relative to TRC, foraging up to depths of 18 metres, while TRC often occupy depths up to 6 metres (Ribbink et al, 1983).…”
Section: Morphological Variation Among Hybrids Mimics Variation Obsmentioning
confidence: 57%
“…1 & 3). This may reflect the rare hunting strategy of this species for nocturnal shrimp prey (also see Lloyd et al 2021 for a nocturnal Malawi cichlid). S. mongo were only observed and captured by seine net after twilight hours beginning around 19:00 hours.…”
Section: Resultsmentioning
confidence: 99%
“…However, the remaining resource specializations are particularly rare among African cichlids. Nocturnality has only been documented once out of thousands of Malawi cichlids (Lloyd et al 2021) and spongivory is only qualitatively reported from Coptodon spongotroktis in Lake Bermin, Cameroon (Stiassny et al 1992). In general, our findings align with the major trophic strategies and specialists outlined by Trewavas et al (1972), providing quantitative data on the differences in dietary component proportions between species.…”
Section: Mongo) and Specialists On Trichopteran (Caddisfly) Larvae (S Pindu) And Plants (K Eisentrauti)mentioning
confidence: 99%
“…A diversity of lifestyles can increase the chances of survival in heterogeneous habitats and can help securing the persistence of the population. Phenotypic diversity can further reduce competition due to a diversification of resource usage and spatial/temporal niches 67, 68 . Distinct individual phenotypes may be more beneficial in heterogeneous or variable habitats like coral reefs, intertidal shores, forest or urban areas that provide a higher potential for different lifestyles 22, 69 .…”
Section: Discussionmentioning
confidence: 99%